Can the response to a platinum-based therapy be predicted by the DNA repair status in non-small cell lung cancer?. (July 2016) - Macerelli, Marianna; Ganzinelli, Monica; Gouedard, Cedric; Broggini, Massimo; Garassino, Marina Chiara; Linardou, Helena; Damia, Giovanna; Wiesmüller, Lisa
Highlights: DNA repair status is important for platinum compound activity in lung cancer. No reliable biomarker of platinum compound activity exists for selecting lung patients. One single DNA repair biomarker is inadequate/insufficient to define responding patients. Abstract: Preclinical evidence has been accumulating on the impact of the DNA repair status on the sensitivity/resistance to anticancer agents in different tumor types, including lung cancer. The possibility to predict the response to therapy, and specifically to platinum agents, based on tumor specific DNA repair functionality would enable to tailor its use only in those patients with maximum chances to respond, avoiding the burden of toxicity in those ones with lesser chances. We here reviewed the clinical evidence on the prognostic role of DNA repair markers and/or functional assays in predicting the response to a platinum-based chemotherapy in lung cancer patients. Consequently, we focused on those proteins involved in pathways repairing platinum induced DNA inter-strand and intra-strand crosslinks. Most promising clinical trials targeting the nucleotide repair protein ERCC1 in non-small cell lung cancer later on suffered from serious drawbacks. Nevertheless, these results spurred a variety of preclinical studies on a multitude of alternative DNA repair markers. However so far, no one of the analyzed DNA repair markers can be considered a reliable and mature biomarker for selecting patients. We discuss the reasons for such failure which discloses novel strategies for the future.